(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
The article covers the topic "Philosophical Factors of Personality Development in New Uzbekistan". It analyzes the role of the individual in the social and spiritual development of society, philosophical approaches to ensuring his development. The article presents philosophical views aimed at the spiritual and moral upliftment of the individual in the context of contemporary political, economic and cultural changes in Uzbekistan. In the new Uzbekistan, the main philosophical factors in the formation of personality are noted in parallel with the changes of society.